Relationship of Gadget Use With Cognitive Levels in Children of Basic School Age (A Study on Students of SD Negeri 7 Kepanjen) - Muzaharyadhi, Langit Susventa (Health Frontiers: Multidisciplinary Journal for Health Professionals, 2023)
In this case, the use of gadgets for elementary school aged children (7-12 y.o) will in some degree affect cognitive levels. This can be seen from the achievement of the achievement value of children in school. Based on preliminary study conducted in Elementary School 7 Kepanjen, obtained the results of a total of 40 respondents as many as 33 children already have their own smartphone and the average use of the majority of gadgets over 3 hours. Meanwhile, more than 30 children admitted to using gadgets for the purposes of playing games and doing tasks. The purpose of research is to know the relationship of using gadget with cognitive level of elementary school age children in SD Negeri 7 Kepanjen. This research uses descriptive analytic descriptive research design and use cross sectional data retrieval. Sampling technique in this research using simple random sampling counted 60 respondents. Research data from a total of 60 respondents as much as 19 (32%) of respondents who categorized the use of high gadget decreased at cognitive level. In contrast, as many as 33 (60%) of children in the category of use were getting good cognitive value. The results were analyzed by Spearman Rank statistic test obtained significance (p)0.001 = (p) < 0.05 which means there is a significant correlation or relationship between variable use of gadgets with cognitive level variables. Based on research the use of gadgets for children should be more limited to avoid the impact and decrease on the cognitive level of children.